2016
DOI: 10.1016/j.jcrimjus.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Changes in inmates' substance use and dependence from pre-incarceration to one year post-release

Abstract: Purpose To assess changes in inmates’ misuse of substances from pre- to post-incarceration. Methods In Study 1, professionals (n = 162) and laypersons (n = 50) predicted how jail inmates’ substance misuse would change from pre-incarceration to post-release. In Study 2, a longitudinal study of 305 jail inmates, we examined actual changes in substance use and dependence from pre-incarceration to the first year post-incarceration, as well as whether changes varied as a function of demographic, criminal justice,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 59 publications
(62 reference statements)
0
13
0
2
Order By: Relevance
“…In addition, among those imprisoned for drug-related crimes and not treated during their prison term, the majority relapse within the year following release [ 3 ]. A recent study confirms that 60% of former inmates met at least one criterion of the Diagnostic and Statistical Manual of Mental Disorders (DSM 5) for substance dependence at one year post-release [ 4 ].…”
Section: Introductionmentioning
confidence: 96%
“…In addition, among those imprisoned for drug-related crimes and not treated during their prison term, the majority relapse within the year following release [ 3 ]. A recent study confirms that 60% of former inmates met at least one criterion of the Diagnostic and Statistical Manual of Mental Disorders (DSM 5) for substance dependence at one year post-release [ 4 ].…”
Section: Introductionmentioning
confidence: 96%
“…3 In a sample of 18 000 formerly incarcerated veterans in contact with VA health care, half were diagnosed with at least one SUD, 40% of which were actively engaging in SUD treatment. 5 Although prison may serve as a period of enforced sobriety, 6 and in fact rates of drug use before incarceration may be higher than those post-release, 7 it remains that substance abuse persists significantly after release from prison-particularly within the first months. One study indicated that 20% of adult prisoners used illicit drugs in the first year upon release.…”
mentioning
confidence: 99%
“…Although prison may serve as a period of enforced sobriety, 6 and in fact rates of drug use before incarceration may be higher than those post-release, 7 it remains that substance abuse persists significantly after release from prison—particularly within the first months. One study indicated that 20% of adult prisoners used illicit drugs in the first year upon release.…”
mentioning
confidence: 99%
“…Numerosos trabajos han sido dedicados al análisis de los antecedentes y consecuencias de la estancia en prisión en la vida de las personas presas o ex presas, en materias tan diversas como el consumo de sus-tancias (entre otros, Hazel, Yoon y Hayes, 2017; Tangney et al, 2016;Merrall et al, 2010;Farrell y Marsden, 2007), la salud física y/o mental (p.e., Thomas, Spittal, Heffernan, Taxman, Alatis y Kinner, 2016;Cutcher, Degenhardt, Alati y Kinner, 2014;Kinner y Wang, 2014;Schnittker y Andrea, 2007), la reinserción social y laboral (p.e., Rovira i Sopeña, 2016; Jacobs Valentine y Redcross, 2015; Owens, 2009) o la reincidencia y el reingreso en prisión (p.e., Thomas, Spittal, Taxman y Kinner, 2015), por citar algunas. Se trata de cuestiones que a menudo se entrelazan, con frecuentes relaciones de interdependencia.…”
Section: Introductionunclassified